Heteronuclear Mn–Ca/Sr complexes, and Ca/Sr EXAFS spectral comparisons with the Oxygen-Evolving Complex of Photosystem II() - Mishra, Abhudaya (2007)
Heterometallic Mn–Ca and Mn–Sr complexes have been prepared and employed as model complexes for Ca and Sr EXAFS spectral comparisons with the Oxygen-Evolving Complex (OEC) of Photosystem II (PS II); these have revealed similarities that support the presence of at least one O atom bridge between the Mn and Ca/Sr in the OEC.